Diffuse idiopathic pulmonary neuroendocrine cell hyperplasia syndrome - Rossi, Giulio; Cavazza, Alberto; Spagnolo, Paolo; Sverzellati, Nicola; Longo, Lucia; Jukna, Agita; Montanari, Gloria; Carbonelli, Cristiano; Vincenzi, Giada; Bogina, Giuseppe; Franco, Renato; Tiseo, Marcello; et al. (The European respiratory journal, 2016)
The term diffuse idiopathic pulmonary neuroendocrine cell hyperplasia (DIPNECH) may be used to describe a clinico-pathological syndrome, as well as an incidental finding on histological examination, although there are obvious differences between these two scenarios. According to the World Health Organization, the definition of DIPNECH is purely histological. However, DIPNECH encompasses symptomatic patients with airway disease, as well as asymptomatic patients with neuroendocrine cell hyperplasia associated with multiple tumourlets/carcinoid tumours. DIPNECH is also considered a pre-neoplastic lesion in the spectrum of pulmonary neuroendocrine tumours, because it is commonly found in patients with peripheral carcinoid tumours. In this review, we summarise clinical, physiological, radiological and histological features of DIPNECH and critically discuss recently proposed diagnostic criteria. In addition, we propose that the term “DIPNECH syndrome” be used to indicate a sufficiently distinct patient subgroup characterised by respiratory symptoms, airflow obstruction, mosaic attenuation with air trapping on chest imaging and constrictive obliterative bronchiolitis, often with nodular proliferation of neuroendocrine cells with/without tumourlets/carcinoid tumours on histology. Surgical lung biopsy is the diagnostic gold standard. However, in the appropriate clinical and radiological setting, transbronchial lung biopsy may also allow a confident diagnosis of DIPNECH syndrome.